Evaluation of Quantity and Hyperhydricity of Cocoa Somatic Embryo Obtained from Solid Culture, Liquid Culture, and Sequence Subculture - Sulistyani Pancaningtyas (Indonesian Coffee and Cocoa Research Institute, 2013)
Research aimed to study the effect of solid culture, liquid culture, and sequence subculture on quantity and hyperhydricity of somatic embryo wascarried out at Laboratory of Biotechnology, Indonesian Coffee and Cocoa Research Institute. Materials used in this study were embryogenic callitransferred on somatic embryos expression both in solid and liquid media with the same media composition, namely MS medium with the addition ofAdenine (0.025 mg/L). Gelling agent used in solid media was gelrite (3 g/L). Clones used in this study was Sca 6. This research consisted of two trials, namely1) effect of medium type (solid and liquid), and 2) sequence subculture (four subcultures). This results showed that the production of somatic embryosin liquid medium was higher than in the solid medium. Regeneration of somatic embryos on solid medium culture showed the highest percentage of abnormality embryos due to hyperhydricity at the cotyledonary phase 60%. Meanwhile, the regeneration of somatic embryos in liquid culture showed the highest percentage of abnormality embryos due to hyperhydricity at the globular and cotyledonary phase 37%. Frequent subculture increased abnormal embryos and decreased the number of somatic embryos.Key words: Cacao, hyperhydricity, somatic embryos, solid culture, liquid culture, subculture, in vitro.